2005
DOI: 10.1128/ec.4.7.1166-1174.2005
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae Rab-GDI Displacement Factor Ortholog Yip3p Forms Distinct Complexes with the Ypt1 Rab GTPase and the Reticulon Rtn1p

Abstract: Rab GTPases are crucial regulators of organelle biogenesis, maintenance, and transport. Multiple Rabs are expressed in all cells, and each is localized to a distinct set of organelles, but little is known regarding the mechanisms by which Rabs are targeted to their resident organelles. Integral membrane proteins have been postulated to serve as receptors that recruit Rabs from the cytosol in a complex with the Rab chaperone, GDI, to facilitate the dissociation of Rab and GDI, hence facilitating loading of Rabs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
53
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 54 publications
6
53
0
Order By: Relevance
“…To gain insight into the physiological role of AtPRA1.B6, the effect of high expression levels of AtPRA1.B6 on anterograde trafficking of various cargo proteins was examined. In a previous study, overexpression of Yip3 in yeast resulted in an inhibition of anterograde trafficking (Geng et al, 2005). A similar observation was made when Yip6b/GTRAP3-18 was expressed in animal cells (Ruggiero et al, 2008).…”
supporting
confidence: 50%
See 3 more Smart Citations
“…To gain insight into the physiological role of AtPRA1.B6, the effect of high expression levels of AtPRA1.B6 on anterograde trafficking of various cargo proteins was examined. In a previous study, overexpression of Yip3 in yeast resulted in an inhibition of anterograde trafficking (Geng et al, 2005). A similar observation was made when Yip6b/GTRAP3-18 was expressed in animal cells (Ruggiero et al, 2008).…”
supporting
confidence: 50%
“…Furthermore, overexpression of Yip3p causes ER membrane proliferation, a well-known phenotype resulting from the inhibition of anterograde trafficking at the ER (Kaiser and Schekman, 1990). These results raise the possibility that Yip3p plays a role in the biogenesis of coat protein complex II (COP II) vesicles at the ER in yeast (Geng et al, 2005). Thus, the biological role of PRA1 has not been fully characterized.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…It has been reported that Pra1 protein has a large COOH-terminal hydrophobic region, and it binds multiple Rabs (Calero et al, 2002) and that catalyzes the dissociation of endosomal Rab-Gdi complexes in S. cerevisiae ( Sivars et al, 2003). In S. cerevisiae, the overexpression of Yip3p (Pra1p) inhibits cellular growth, and it can play a crucial role in vesicles trafficking ( Geng et al, 2005).…”
Section: Hyphal Growth Machinery and Its Transcriptional Regulationmentioning
confidence: 99%